The shear bond strength of orthodontic brackets after surface conditioning of Zirconia, Ceramic and E. max models - Khalid, Amina R; Al Jwary, Enas T (Edelweiss Applied Science and Technology, 2024)
The current study aims to evaluate the shear bond strength (SBS) of metal orthodontic brackets after surface conditioning by hydrofluoric acid (HF) and aluminum oxide air abrasion (Al2O3) and using two prime types and to determines the adhesive remnant index (ARI). We compared the bond strength of different types of models (full glazed zirconia, ceramic faced zirconia and E. max faced zirconia) with different surface conditioning methods for attaching metal orthodontic brackets. The study used 60 models for each material, divided into subgroups based on the type of prime material and surface preparation method. The bond strength was measured using a universal testing machine and the results were analyzed using statistical software. Shear bond strength of the Aluminum oxide was statistically (p<0.05) higher than the hydrofluoric acid and control groups in all groups (full glazed zirconia, ceramic faced zirconia and E. max faced zirconia). The Assure® Plus primer with Aluminum oxide surface treatment give rise to the highest shear bond strength than 3M™ Transbond™ XT, while there was no significant difference between Assure® Plus and 3M™ Transbond™ XT primer for both control and hydrofluoric acid groups. The highest shear bond strength was obtained with Aluminum oxide conditioning method for all types of ceramic materials used in this study.